Static and cyclic stretching: Their different effects on the passive torque-angle curve - Nordez, A.; McNair, P. J.; Casari, P.; Cornu, C. (Journal of Science and Medicine in Sport, 2010)
The findings of previous research indicate that the passive torque-angle curve may be different according to whether individuals have undertaken cyclic or static stretching. To date, no authors have compared these curves in the same subjects. We hypothesised that static stretching would lead to a constant change in range of motion across torque levels with the shape of the curve being unchanged, while cyclic stretching would change the shape of the curve. To test this hypothesis, eight subjects performed five passive knee extension/flexion cycles on a Biodex® dynamometer at 5° s-1 to 80% of their maximal range of motion before and after a static stretching protocol. The difference in angle between pre and post stretching torque-angle curves was calculated at 11 levels of torque from 0% to 100% of the maximal torque with a 10% increment. The mean change in angle across these 11 torque levels was then calculated. The findings showed that after static stretching a relatively constant mean change of 5.2° was noted across torque levels. In contrast, after cyclic stretching the angle change depended upon the torque level with greater change observed toward the start of the range of motion. The findings indicated that different mechanisms were operating depending upon the type of stretching procedure performed. Changes in muscle resting length and thixotropy were thought to be responsible.